Réponses

Meilleure réponse !
2014-10-30T13:21:35+01:00
A) x^4-13x²+36=0  (X=x²)
X²-13X+36=0
delta= 25
X1=9  X2=4
x=3 ou x=-3 ou x=2 ou x=-2

b) x^4-5x²+4=0  (X=x²)
X²-5X+4=0
delta= 9
X1= 4  X2= 1
x=2 ou x=-2 ou x=1 ou x=-1

c) x^4+x²-2=0  (X=x²)
X²+X-2=0
delta= 9
X1=4  X2=1
x=2 ou x=-2 ou x=1 ou x=-1

d) 9x^4-85x²+196=0  (X=x²)
9X²-85X+196=0
delta= 169
X1=49/9  X2=4
x=7/3 ou x=-7/3 ou x=2 ou x=-2

e) 3x^4-7x²+4=0  (X=x²)
3X²-7X+4=0
delta=1
X1=4/3  X2=1
x=racine4/3  ou x=-racine4/3  ou x=1 ou x=-1

f) x²+1/x²-6=0 
pour celle la je ne sais pas par contre